WELFARE IN ISLAMIC PERSPECTIVE: A REVIEW OF ISLAMIC PRODUCTIVITY AND MICROECONOMICS - Muhamad Agus Alfiyan Nur Ahmada; Gayuh Kawedar; Ahmad Fatan Al Banna; Siti Itsna Syamsiyah; Binti Nur Asiyah; Mashudi Mashudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of economic productivity, Islamic consumption, and Islamic production on welfare in Indonesia in 2023. Social inequality and unequal distribution of welfare remain fundamental issues, raising profound questions about the continued increase in economic growth that has not been fully absorbed by the lower levels of society. This study uses quantitative methods from secondary data obtained from the Central Statistics Agency (BPS), National Zakat Agency (BAZNAS), and halal.kemenperin.go.id. This study sample covers 34 provinces out of a population of 38 provinces in Indonesia in the 2023 period, due to limited data availability. Multiple linear regression was used for data analysis, while SPSS version 25 was utilized for data processing. The results of this study indicate that, simultaneously, economic productivity, Islamic consumption, and Islamic production have a positive and significant effect on welfare. Partially, economic productivity has a positive but insignificant effect on welfare. Then, partially, Islamic consumption has a negative but insignificant effect on welfare. And partially, Islamic production has a positive and significant effect on welfare. This finding confirms that prosperity in Islamic economics is not only determined by economic growth alone, but also by the blessings of balanced and fair productive and consumption activities.